2010
DOI: 10.1590/s0102-695x2010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da relação estrutura-atividade de saponinas hemolíticas e/ou imunoadjuvantes mediante uso de análise multivariada

Abstract: RESUMO:Entre as diversas atividades biológicas relatadas para as saponinas, merecem destaque aquelas relacionadas ao aumento da resposta imune e a ruptura das membranas dos eritrócitos. No desenvolvimento de vacinas, ambas as propriedades exercem atividades antagônicas, contudo, as informações sobre as relações estrutura-atividade são relativamente escassas e, às vezes, conflitantes. O presente trabalho visa contribuir no estabelecimento das relações estruturais envolvidas com as atividades imunoadjuvante e he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Saponin compounds were only found in aqueous, methanolic and hydroethanolic extracts. They have several biological activities; the ones that should be highlighted are related to increase in immune response and rupture of erythrocyte membranes, such as immunologic adjuvant and hemolytic activities (Kaiser, Pavei, & Ortega, 2010). Soares et al (2016) identified saponin groups in aqueous extract from S. odoratissima leaves.…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…Saponin compounds were only found in aqueous, methanolic and hydroethanolic extracts. They have several biological activities; the ones that should be highlighted are related to increase in immune response and rupture of erythrocyte membranes, such as immunologic adjuvant and hemolytic activities (Kaiser, Pavei, & Ortega, 2010). Soares et al (2016) identified saponin groups in aqueous extract from S. odoratissima leaves.…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…Estudos apontam sua ação antimicrobiana, reparação de tecidos e regularização de proteínas e enzimas, grupos de taninos estão sendo estudados minuciosamente, tendo por finalidade encontrar uma droga efetiva contra o vírus HIV (Brunet et al, 2003). Além disso, taninos constituem uma das classes de maior destaque devido a sua ampla distribuição no reino vegetal e suas importantes atividades biológicas, dentre elas antibacteriana e antifúngica (Diniz, 2006;Kaiser et al, 2010).…”
Section: Resultsunclassified
“…Among the secondary metabolites produced by plants, saponins constitute one of the most prominent classes due to their wide distribution in the plant kingdom and their important biological activities (Kaiser et al 2010). Hecogenin, which is isolated from Agave sisalanap, belongs to the class of steroidal saponins or sapogenins, in dried sisal leaves (Cripps and Bluden 1978;Zullo et al 1984;Zullo et al 1989) anti-in ammatory (Ingawale and Patel, 2016) and gastroprotective ).…”
Section: Introductionmentioning
confidence: 99%